Direct current shock and antidysrhythmic drugs - Szekely, Paul (1970)
A review is given of 457 episodes of atrial fibrillation that occurred in 318 patients and were treated by DC shock. Antidysrhythmic drugs, such as quinidine, procainamide, and propranolol, given singly or in combination, were used concomitantly in 389 instances, and DC shock alone was given in 68 instances. The combined effects of quinidine and DC shock, and of procainamide and DC shock were studied in the experimental animal. Combined DC shock and drug therapy gave a higher conversion rate than DC shock alone, and a statistically significant difference was found in respect of the group of patients receiving procainamide and propranolol together (p<0.01). Antidysrhythmic drugs failed on the whole to reduce the incidence of DC shock-induced dysrhythmias. However, the incidence of certain digitalis and DC shock-induced dysrhythmias was significantly less when propranolol and procainamide were given as pretreatment than when procainamide or quinidine was given alone (p<0.01). In animal experiments, quinidine had no protective action against digitalis and DC shock-induced ectopic tachycardias. Clinical and experimental observations suggest that the cardiotoxicity of these drugs may be enhanced by DC shock. Immediate or delayed post-shock rhythm disorders can be drug related and, therefore, great caution should be exercised in the use of antidysrhythmic drugs in conjunction with DC shock therapy.